MENGATASI PERAN PEMERINTAH DALAM PENYEDIA AKSES PELAYANAN PUBLIK - Bagus Rangga Prayoga; Rafli Mahrum; Hayat, Hayat (Cahaya Ilmu Bangsa, 2025)
The central government or local government has a very big role in the fulfillment of the principle of public services, for example in terms of education, health, socio-economic, and transportation, but in all sectors in the fulfillment of improved services, one is the increased access to public services that have not especially in areas that are archipelagos or remote areas. Success in the delivery of public services one can be measured from the access of its public services, so that not being able to get easy access in public services will cause problems that will affect the welfare of the whole society. Therefore, the role of government is very large in the implementation of public service oriented to the community.